PENGEMBANGAN PERMAINAN EDUKATIF MATERI HUKUM GRAVITASI NEWTON - Eko Hari Tiarto; Agus Suyatna; Feriyansyah Sesunan (Jurnal Pembelajaran Fisika, 2013)
The purpose of this research development is to develop an educational game for students of class X SMA Negeri 1 Gadingrejo that can be played in the confirmation phase of learning in classroom. This research development used research methods adapted from the Sugiyono’s model and instructional media development procedures Sadiman et al. The final products is an educational game of Newton's law of gravity material that can be played in the confirmation phase of learning in classroom to review the material and practice questions for students. This educational game consists of a game board, pawns, zonkah, question exercise cards, game rule, hand out answered questions, and student record sheets. The conclusion of this research is the educational game Newton’s law of gravity material has developed and the quality of this educational game is very interesting, easy, and very usefull. Furthermore, this educational game is effective to be used in learning in classroom.Key words: research development, educational game, and Newton's law of gravity.